Angiogenic activity in patients with psoriasis is significantly decreased by Goeckerman's therapy - Andrýs, Ctirad; Borská, Lenka; Pohl, David; Fiala, Zdeněk; Hamáková, Květoslava; Krejsek, Jan (Archives of dermatological research, 2007)
Goeckerman's therapy (GT) of psoriasis is based on daily application of pharmacy grade coal tar on affected skin with subsequent exposure to UV light. Goeckerman's therapy is still the first line therapy of psoriasis in the Czech Republic because of its low cost and long-term efficacy. Disturbances in angiogenic activity are characteristic for the immunopathogenesis of psoriasis. An abnormal spectrum of cytokines, growth factors and proangiogenic mediators is produced by keratinocytes and inflammatory cells in patients suffering from the disease. The aim of this study was to evaluate the influence of GT of psoriasis on angiogenic activities by comparing serum levels of vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) in 44 patients with psoriasis in peripheral blood samples collected before and after therapy. Forty otherwise healthy blood donors serve as a control group. The efficacy of GT was delineated by psoriasis area and severity index (PASI). The disease activity was significantly diminished by GT (P < 0.001). The serum levels of both VEGF and bFGF were statistically significantly correlated to PASI value in patients before the treatment by GT. The serum levels of VEGF (329.4 +/- 125.5 microg/ml) and bFGF (10.2 +/- 5.04 pg/ml) in patients before GT were significantly higher than those measured in healthy blood donors (VEGF 236.4 +/- 55.9 pg/ml, bFGF 7.3 +/- 3.7 pg/ ml). The serum levels of both VEGF and bFGF were significantly diminished by GT. The level of VEGF dropped from 329.4 +/- 125.5 pg/ml before GT to 278.5 +/- 109.9 pg/ml after GT (P = 0.0042) and the level of bFGF fell from 10.2 +/- 5.04 to 7.78 +/- 4.5 pg/ml (P = 0.019). Comparing to healthy controls, the serum level of bFGF in psoriasis patients was normalised (P = 0.5723) after GT. In contrast, the serum level of VEGF remained significantly increased in psoriasis patients after GT in comparison with healthy blood donors (P = 0.0319). In conclusion, we found that the angiogenic potential which is abnormally increased in patients with psoriasis is significantly alleviated by GT.
Keywords: Vascular Endothelial Growth Factor A; kombinovaná terapie; Ultraviolet Therapy; Humans; lidé středního věku; Fibroblast Growth Factor 2; Psoriasis; dehet uhelný; Female; Aged; kůže; dospělí; psoriáza; financování organizované; Financing, Organized; senioři; lidé; ultrafialové záření; mladiství; Coal Tar; Neovascularization, Pathologic; Adult; ženské pohlaví; stupeň závažnosti nemoci; Male; vaskulární endoteliální růstový faktor A; Middle Aged; Adolescent; Severity of Illness Index; Ultraviolet Rays; Combined Modality Therapy; fibroblastový růstový faktor 2; mužské pohlaví; patologická angiogeneze; Skin; terapie ultrafialovými paprsky